Effect of bariatric surgery on carotid intima-media thickness: A meta-analysis based on observational studies - Zhou, Hui; Jin, Yangli; Dai, Senjie; Dai, Chenglong; Ye, Xia (Frontiers in Surgery, 2023)
Objective This meta-analysis aimed to investigate the effect of bariatric surgery on CIMT in people with obesity. Methods PubMed, Web of Science, Embase, and the Cochrane Library were searched for observational studies assessing the effect of bariatric surgery on CIMT from inception to August 2022. Mean difference (MD) and 95% confidence intervals were calculated to assess CIMT. Results A total of 23 studies, including 1,349 participants, were eligible to participate in this meta-analysis. The results revealed that CIMT was significantly decreased at 6 months, 12 months, and more than 18 months after bariatric surgery compared with baseline (6 months: MD = 0.09; P < 0.01; 12 months: MD = 0.12; P < 0.01; more than 18 months: MD = 0.14; P = 0.02). Meanwhile, laparoscopic Roux-en-Y gastric bypass (LRYGB) seemed to be more effective than laparoscopic sleeve gastrectomy (LSG) in lowering CIMT in terms of the type of surgery (LSG: MD = 0.11; P < 0.01; LRYGB: MD = 0.14; P < 0.01). Lastly, the benefits of bariatric surgery on CIMT was independent of gender (Male: MD = 0.06; P = 0.04; Female: MD = 0.08; P = 0.03). Conclusions Bariatric surgery is consistently effective in reducing CIMT in people with obesity.